Application of Flow Cytometry in the Early Diagnosis of Neonatal Sepsis - Aydin, Mustafa; Barut, Sumeyye; Akbulut, H. Handan; Ucar, Sit; Orman, Aysen (Assoc Clinical Scientists, 2017)
Goals. To raise awareness of the utility of flow cytometric detection of inflammatory markers in the early diagnosis of neonatal sepsis. Procedures. In accordance with the Tollner scoring system, cases with >= 10 points are accepted as having clinical sepsis and cases with 0-4 points as having no sepsis. The study group consisted of 50 newborns with clinical sepsis as well as a control group of 50 newborns without sepsis. In all cases, blood counts, C-reactive protein (CRP) levels, and procalcitonin (PCT) levels were recorded. Additionally, the cluster of differentiation (CD) 64, CD11b, and CD62L adhesion molecules and the presence of the human leukocyte antigen HLA-DR on monocyte and neutrophil surfaces were examined by flow cytometry. Results. The levels of acute-phase reactants CRP and PCT were significantly higher in the study group than in the control group (p<0.05). The cell adhesion molecules CD11b and CD64 and the human leukocyte antigen HLA-DR were significantly higher in the study group (p<0.05); CD62L levels were similar to those in the control group (p>0.05). Furthermore, receiver operating characteristic analysis indicated that neutrophil CD11b (nCD11b) is a diagnostic marker for neonatal sepsis (area under the curve [AUC]: 0.72, 95% confidence interval [CI]: 0.62-0.82, p<0.001). The sensitivity, specificity, and positive predictive value (PPV) for nCD11b were 72%, 68%, and 58.4%, respectively. Similarly, monocyte CD11b (mCD11b) positivity was found to be diagnostic (AUC 0.77, 95% CI: 0.68-0.87, p<0.001). The sensitivity and specificity for mCD11b were 72% and 68%, respectively. In addition, the sensitivity, specificity, and PPV for nHLA-DR were 62%, 60%, and 60.8%, respectively. Conclusion. In addition to acute-phase proteins, cell surface antigens such as CD11b, CD64, and HLA-DR should be used in routine investigations for the early diagnosis of neonatal sepsis. Such usage in combination with acute-phase reactants may enhance diagnostic accuracy.
Keywords: Newborn infant; sepsis; biomarker; C-reactive protein; procalcitonin; flow cytometry; CD11b; CD64; CD62L; HLA-DR